2020
DOI: 10.1177/1120700020926986
|View full text |Cite
|
Sign up to set email alerts
|

Elevated HbA1c is not a risk factor for wound complications following total joint arthroplasty: a prospective study

Abstract: Background: Controversies exist regarding the association of elevated serum glycated haemoglobin (HbA1c) levels and postoperative surgical site infection (SSI) or prosthetic joint infection (PJI) in the setting of total hip and knee arthroplasty (THA and TKA). The purpose of the current study was to determine the prevalence of unknown and uncontrolled diabetes mellitus (DM) in a consecutive series and to investigate the association between postoperative wound complications or SSI/PJI and elevated HbA1c in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…However, due to the rich blood supply around the hip joint, intraoperative soft tissue dissection and intracavitary marrow expansion are associated with intraoperative hemorrhage, which requires blood transfusion to maintain effective circulating blood volume [ 1 3 ]. Although blood transfusion relieves the organ burden caused by massive blood loss, patients are predisposed to complications such as immune reaction and autohemolysis [ 4 , 5 ], especially for those with underlying diseases such as diabetes mellitus where blood transfusion is insufficient to reduce their surgical risk. Diabetic patients generally have poor surgical tolerance due to the long-term hyperglycemia of the organism, and massive intraoperative blood loss leads to cardiac and renal dysfunction and poor wound healing, thereby increasing the perioperative mortality of patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the rich blood supply around the hip joint, intraoperative soft tissue dissection and intracavitary marrow expansion are associated with intraoperative hemorrhage, which requires blood transfusion to maintain effective circulating blood volume [ 1 3 ]. Although blood transfusion relieves the organ burden caused by massive blood loss, patients are predisposed to complications such as immune reaction and autohemolysis [ 4 , 5 ], especially for those with underlying diseases such as diabetes mellitus where blood transfusion is insufficient to reduce their surgical risk. Diabetic patients generally have poor surgical tolerance due to the long-term hyperglycemia of the organism, and massive intraoperative blood loss leads to cardiac and renal dysfunction and poor wound healing, thereby increasing the perioperative mortality of patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have investigated the impact of diabetes on outcomes after total joint arthroplasty. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] The ideal future study of this topic might include measures of preoperative and perioperative glycaemic control, preoperative and perioperative use of insulin, and THA-specific outcomes at longer follow-up. Such a study might determine which data have the greatest predictive value and might identify modifiable risk factors for future quality improvement initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…20,32,36,39,42 There was a total of five prospective studies, of which four did not find a correlation between preoperative HbA1c levels and increased incidence of SSI. 20,24,27,41,43 The single prospective study that did find a positive correlation involved 50 patients who underwent a variety of elective surgical operations. 20 The authors reported that patients with HbA1c >7% had a higher incidence of SSI, but also noted that these same patients had wider postoperative glycemic variability and higher preoperative and postoperative blood glucose levels.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%